Investigation on the Adsorption and Photooxidation of Glycerol at TiO2 Nanotubular Arrays - Simonetta Palmas; Anna Da Pozzo; Michele Mascia; Annalisa Vacca; Roberto Matarrese (International Journal of Photoenergy)
A study is presented on the adsorption of glycerol at TiO2 as well as on its oxidative process during the contemporary water Photoelectro-splitting for hydrogen production. A deepening in the understanding on the working mechanism of the TiO2 nanotubular photoanodes and on the interactions between glycerol and these structures has been gained through photocurrent tests, voltammetric scans, and EIS analysis. A range of wavelength of the incident radiation is investigated from 340 to 400 nm at which the effect of glycerol on the photocurrent is measured. Quantitative analysis of the EIS results is performed by the equivalent circuit approach.